PENGARUH MODAL INTELEKTUAL, GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERBANKAN DI BURSA EFEK INDONESIA - Kadek Agustini Dwi Putri; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (JUIMA : JURNAL ILMU MANAJEMEN, 2023)
: In conducting business operations, it is essential for every company to possess the ability to effectively manage its assets in order to fulfill its business goals. Financial performance is one of the measures indicating the success of a business. Financial performance, proxied by Return On Assets (ROA), is used to measure a company's effectiveness in generating profits by utilizing its assets. The greater a company's ROA, the better its position in terms of asset utilization. This study aims to explain the influence of intellectual capital, board of directors, managerial ownership, and company size on financial performance in Banking Companies listed on the Indonesia Stock Exchange (IDX). The population of this study comprises all Banking Companies listed on the IDX from 2020 to 2022, totaling 47 companies. Sampling was conducted using purposive sampling technique, resulting in a sample of 18 companies. The analytical technique employed to test the hypotheses is multiple linear regression analysis. The research findings indicate that intellectual capital has a positive and significant influence on company financial performance (return on assets). However, the board of directors, managerial ownership, and company size do not influence financial performance (return on assets) in banking companies.